2015
DOI: 10.1016/j.molimm.2015.07.001
|View full text |Cite|
|
Sign up to set email alerts
|

Insights into the effector functions of human IgG3 in the context of an antibody targeting transferrin receptor 1

Abstract: The transferrin receptor 1 (TfR1) is involved in cellular iron uptake and regulation of cell proliferation. The increased expression of TfR1 observed in malignant cells, compared to normal cells, together with its extracellular accessibility, make this receptor an attractive target for antibody-mediated cancer therapy. We have developed a mouse/human chimeric IgG3 specific for human TfR1 (ch128.1), which shows antitumor activity against certain malignant B cells in vitro through TfR1 degradation and iron depri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Our recombinant antibody (IgG3KVH) showed stronger binding to C1q than IgG1. Previously, it was reported that residues D270, K322, P329, and P331 in the CH2 domain constitute the human C1q binding site of the Fc region . However, the substitutions introduced into IgG3KVH were all within the CH3 region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recombinant antibody (IgG3KVH) showed stronger binding to C1q than IgG1. Previously, it was reported that residues D270, K322, P329, and P331 in the CH2 domain constitute the human C1q binding site of the Fc region . However, the substitutions introduced into IgG3KVH were all within the CH3 region.…”
Section: Discussionmentioning
confidence: 99%
“…For the IgG3KV antibody, FcγRIIIa binding activity was drastically decreased. It has also been shown that IgG1 binding to FcγRIIIa is mediated through the hinge and CH2 regions and that the CH3 domain does not directly affect binding . A previous study indicated that the CH3 and CH2 domains of the IgG2 antibody interacted via L251 in the CH2 region and residues M428, H429, E430, and H435 in the CH3 domain .…”
Section: Discussionmentioning
confidence: 99%
“…ch128.1 (IgG3/κ) and the ch128.1 triple mutant L234A/L235A/P329S were produced in murine myeloma cells and affinity purified as described (27, 28). Mutations were previously generated on the ch128.1 heavy chain γ3 expression vector to disrupt binding to FcγRs and complement component C1q (27).…”
Section: Methodsmentioning
confidence: 99%
“…Another example is an Fc-engineered anti-CD70 IgG1 that contains five mutations (C226S/C229S/E233P/L234V/L235A) and shows decreased ADCP activity ( 123 ). Furthermore, a human IgG3 targeting the transferrin receptor 1 (TfR1) containing only two mutations (L234A/L235A) showed decreased ADCC activity against TfR1 expressing target cells, an effect that was increased by the addition of a third mutation P329S ( 125 ). However, the P329S single mutant showed no effect on ADCC ( 125 ).…”
Section: Modulating Fc-dependent Effector Functionsmentioning
confidence: 99%
“…Point mutations at any one of these sites in rituximab decreased CDC activity, but not ADCC or binding to FcRn ( 129 ). In a human IgG3 targeting TfR1, the P329S mutation abolished CDC activity against TfR1 expressing target cells, but no impaired ADCC was detected with this single mutation ( 125 ).…”
Section: Modulating Fc-dependent Effector Functionsmentioning
confidence: 99%